2005
DOI: 10.1111/j.1439-0442.2005.00758.x
|View full text |Cite
|
Sign up to set email alerts
|

Daily Rhythms of Blood Pressure, Heart Rate, and Body Temperature in Fed and Fasted Male Dogs

Abstract: Daily or circadian rhythmicity in physiological processes has been described in a large number of species of birds and mammals. However, in dogs, most studies have either failed to detect rhythmicity or have found that rhythmicity reflects merely an acute exogenous effect of feeding rather than an autonomous rhythmic process. In the present study, we investigated the rhythmicity of body temperature, blood pressure, and heart rate in dogs fed daily as well as in dogs deprived of food for 60 h. Our results docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…Ten-day-old lamb and foal both show a circadian rhythm of body temperature. This rhythmicity is lacking in blood pressure, as previously observed for heart rate and respiratory rate (Piccione et al, 2005b), may be caused by different control systems, and probably correlates with the incomplete anatomical-functional development of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 81%
“…Ten-day-old lamb and foal both show a circadian rhythm of body temperature. This rhythmicity is lacking in blood pressure, as previously observed for heart rate and respiratory rate (Piccione et al, 2005b), may be caused by different control systems, and probably correlates with the incomplete anatomical-functional development of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 81%
“…We have previously shown that the wave forms of the daily rhythms of body temperature, heart rate, and blood pressure of the dog are not affected by the time of feeding [22]. Water was available ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…recently, the effect of a treadmill exercise program on plasma cortisol hormone level and some physiological and hematological parameters have been evaluated in German shepherd dogs [16,17]. on the other hand, in Beagle dogs, the studies have been limited to evaluation of daily rhythmicity of these parameters [14,18] without considering the response that occurs during exercise. in fact, to the best of our knowledge, there are no available data that originate from standardized studies in Beagles.…”
Section: Introductionmentioning
confidence: 99%